2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8968451
|View full text |Cite
|
Sign up to set email alerts
|

Towards Generalizing Sensorimotor Control Across Weather Conditions

Abstract: The ability of deep learning models to generalize well across different scenarios depends primarily on the quality and quantity of annotated data. Labeling large amounts of data for all possible scenarios that a model may encounter would not be feasible; if even possible. We propose a framework to deal with limited labeled training data and demonstrate it on the application of vision-based vehicle control. We show how limited steering angle data available for only one condition can be transferred to multiple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The unit of measurement we use for online evaluation is the ratio on lane metric adapted from [14]. It gives the ratio of frames the ego-vehicle remains within its own driving lane to the total number of frames.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unit of measurement we use for online evaluation is the ratio on lane metric adapted from [14]. It gives the ratio of frames the ego-vehicle remains within its own driving lane to the total number of frames.…”
Section: Methodsmentioning
confidence: 99%
“…In the point clouds generated from dense depth maps, it may be hard to recognize relevant high-level features like road markings, traffic poles etc. These high level features tend to be important for the model to take the appropriate steering decisions [14]. Moreover, having redundant points in the point cloud which do not yield useful information for the vehicle control model would impose an unnecessary computational burden.…”
Section: A Point Cloud Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…For e.g. a control model trained on images from a sunny weather condition would have difficulty controlling the vehicle in a rainy weather condition even though the domains may be the same [68]. Note that the entire code for training and conducting both offline along with online evaluation is contained in the fol-lowing repository: https://github.com/Dekai21/ Multi_Agent_Intersection.…”
Section: Domain Adaptationmentioning
confidence: 99%
“…Nonetheless, our method for car following is robust against the remaining void regions caused by occlusion or discontinuities in the predicted depth map. [26] showed that the sensorimotor control model focuses on high-level features such as lane markings, and pavement for immediate decision making. Thus, our processed rendered images still contain relevant information for the model to predict correct control commands.…”
Section: B Data Augmentationmentioning
confidence: 99%